2005
DOI: 10.3989/scimar.2005.69n4603
|View full text |Cite
|
Sign up to set email alerts
|

Stock assessment of sardine (<i>Sardina pilchardus</i>, Walb.) in the Adriatic Sea with an estimate of discards

Abstract: SUMMARY:Analytical stock assessment of sardine (Sardina pilchardus, Walb.) in the Adriatic Sea from 1975 to 1999 was performed taking into account the occurrence of discarding at sea of sardine caught by the Italian fleet. We have attempted to model the fishermen's behaviour using data collected by an observer on board fishing vessels. This enabled us to estimate the amounts of discards, which were added to the catches landed, collected by ISMAR-CNR Ancona. Discards were calculated for the period 1987-1999, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 11 publications
(10 reference statements)
2
35
0
Order By: Relevance
“…Discarding does not occur in relevant quantities, as declared by the operators and confirmed in Santojanni et al (2005), so fishing mortality due to discards was not included in the model.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Discarding does not occur in relevant quantities, as declared by the operators and confirmed in Santojanni et al (2005), so fishing mortality due to discards was not included in the model.…”
Section: Methodsmentioning
confidence: 99%
“…Fishing for other pelagics and also "white fish" (Sparidae, Mugilidae, Merlangus merlangus, etc.) takes place occasionally and opportunistically, but it is considered rather rare (Santojanni et al, 2005). The bioeconomic model called MEFISTO is a multispecies, multifleet and multigear simulation model described in detail in Lleonart et al (1999Lleonart et al ( , 2003.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Landings of purse seiners are usually of better quality (fishes are less damaged) and can get a higher price than the landings of trawlers. Discarding by the Adriatic small pelagic fishery has been investigated very little; Santojanni et al (2005) concluded that moderate discarding of sardine can be found in specific geographic zones when the length of the fish is smaller than the market requirements. However, they described fishermen behaviour before the year 2000.…”
Section: Data: the Adriatic Small Pelagic Fisherymentioning
confidence: 99%
“…After FOS data were collated, the next step consisted in estimating an index of relative fish abundance. To do this we followed the classical method based on the use of catch and effort data (Richards and Schnute, 1992;Goñi et al, 1999;Campbell, 2004;Santojanni et al, 2005). MFSTEP satellite and model products were selected and used as explanatory variables.…”
Section: Evaluation Of Anchovy Abundancementioning
confidence: 99%